2022
DOI: 10.1016/j.jksuci.2021.10.001
|View full text |Cite
|
Sign up to set email alerts
|

iVaccine-Deep: Prediction of COVID-19 mRNA vaccine degradation using deep learning

Abstract: Messenger RNA (mRNA) has emerged as a critical global technology that requires global joint efforts from different entities to develop a COVID-19 vaccine. However, the chemical properties of RNA pose a challenge in utilizing mRNA as a vaccine candidate. For instance, the molecules are prone to degradation, which has a negative impact on the distribution of mRNA among patients. In addition, little is known of the degradation properties of individual RNA bases in a molecule. Therefore, this study aims to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…For example, Muneer et al reported an artificial intelligence (AI)-based algorithm to predict degradation at each base of an RNA molecule, with a high speed and efficiency. 450 Kaggle models were able to predict mRNA degradation with an excellent accuracy. 451 Yaish and Orenstein used deep neural networks to predict mRNA degradation dynamics and identified known and novel cis-regulatory sequence elements of mRNA degradation.…”
Section: Theoretical Prediction Of Nucleic Acid Degradationmentioning
confidence: 97%
“…For example, Muneer et al reported an artificial intelligence (AI)-based algorithm to predict degradation at each base of an RNA molecule, with a high speed and efficiency. 450 Kaggle models were able to predict mRNA degradation with an excellent accuracy. 451 Yaish and Orenstein used deep neural networks to predict mRNA degradation dynamics and identified known and novel cis-regulatory sequence elements of mRNA degradation.…”
Section: Theoretical Prediction Of Nucleic Acid Degradationmentioning
confidence: 97%
“…At last, the effective DL models for intrusion detection are deployed in the edge layer. Moreover, the Group Method of Data Handling (GMDH) [ 16 ], Mutual Information (MI) [ 17 ], and the Chi-Sqr statistic techniques [ 18 ] are used to evaluate the effectiveness of dimensionality reduction algorithms. Furthermore, RNN and a subclass of RNN called Bi-directional LSTM are incorporated to evaluate the attack classification performance.…”
Section: Proposed Modelmentioning
confidence: 99%
“…12, No. 5, October 2022: 5589-5599 5592 [33] and forecasting problems [34]. The main parameters of DLNN are the number of input vectors, the number of layers, the number of neurons in each layer.…”
Section: Deep Learning Neural Network (Dlnn)mentioning
confidence: 99%